Strategic planning to invest in human resources as an input to achieve development in the Arab countries . Reading in the experience of Malaysia - djaidja, nabila; djaidja, wifak (Journal of Social Sciences and Humanities, 2021)
This study aimed to highlight the importance of investing in human resources and its role in achieving development in the Arab countries, and how it can be planned strategically to invest in this wealth, which is a measure of the progress of nations, it is known that the developed countries directed the bulk of its investments towards the development of this human wealth and empowerment has Malaysia's experience in developing its human resources has been mentioned as an attempt to benefit from it in the Arab countries by making some suggestions.